T-SHIRT INDIEGUERILLAS SEBAGAI MEDIA KOMUNIKASI VISUAL - Aji Windu Viatra (Besaung : Jurnal Seni Desain dan Budaya, 2017)
Clothing style is often associated with the perception of the identity of the person who describes the class, profession, origin, gender and social. Appearance in the way we dress is interpreted to make a mark against the communicant interaction act indirectly and what should make us behave toward others. Apparel is seen to have a communicative function, in the Science Communication process can communicate through visual and verbal media such material in this study that T-shirts or T-shirts. This study will analyze the T-shirts (T-shirt) Indieguerillas as a medium of visual communication can be a major influence and interpret a t-shirt design that can speak, act and understand the meaning of a sign as desired by the manufacturer of the shirt. Research "T-shirt Indieguerillas As A Media Visual Communication", aims to identify and analyze the meaning of the t-shirt works Indieguerillas that are part of the needs of people using T-shirts as the clothes and trends that explain the identity of one's personal, as well as a visual communication media quite powerful, and as a flexible media information.The main study of this research emphasis on identifying, analyzing the meaning of the work in the form of media Indieguerillas t-shirt. This study using a multidisciplinary approach, the historical approach, aesthetics and semiotics. The method used is qualitative method with descriptive analysis analytic. Data were collected through library research, observation and interviews. The data is then identified, classified, selected, analyzed and interpreted according text and context.Planning studies will be grouped according to the concept works Indieguerillas "Happy + Victim" which will be assessed by looking at the concept of the artwork and design motifs, shapes, characters, colors, and construction techniques. Development and change t-shirt as a medium of visual communication is a part in the discussion of this study, will be reviewed again by analyzing the works t-shirt Indieguerillas containing elements of art and principles of design.Keywords : T-shirt, Art and Design, Visual Communication, Indieguerillas